Nursing management strategies for optimizing SBAR-based bedside handover implementation in an inpatient unit - I Dewa Ayu Rai Netrawati; Frieda Panjaitan; Ratri Ermawati; Samuel M Simanjuntak (School of Health Sciences Al-Ma'arif, 2026)
Background: Bedside handover is a clinical communication strategy that supports continuity of care, patient safety, and patient involvement. The initial assessment in the inpatient unit showed an implementation rate of 68%, nurse–patient interaction during handover of only 33%, non-standardized documentation, and the absence of an SBAR-based bedside handover SOP that consistently involved patients. Objective: This article aimed to evaluate nursing management strategies for optimizing SBAR-based bedside handover implementation in an inpatient unit at a hospital in Jakarta. Methods: This quality improvement study used a pre–post evaluation approach and involved 20 inpatient nurses, including 13 diploma-prepared nurses and 7 professional nurses. The initial assessment included observation, brief interviews, document review, and one FGD with unit nurses. The intervention was implemented through baseline assessment, development of an SBAR-based SOP and documentation format, socialization, training and simulation, appointment of handover champions, supervision, and three monthly audit cycles from August to October 2025. Data were analyzed descriptively. Results: Bedside handover implementation increased from 68% in August to 77% in September and 90% in October. At baseline, patient interaction during handover was 33%, form uniformity was 82%, 50% of nurses reported documentation difficulties, and leadership during handover was documented in 27% of observations. The background and assessment components improved but remained inconsistently communicated. Conclusion: Nursing management strategies involving procedure standardization, training, documentation, handover champions, supervision, and continuous audit contributed to improved SBAR-based bedside handover. Further strengthening of background, assessment, and patient involvement is required to ensure that improved compliance is accompanied by better clinical communication quality.